THE KINETICS OF CONTAMINANTS ACCUMULATION IN THE JET FUEL DURING THE TECHNOLOGICAL PROCESS OF ITS PREPARATION FOR AIRCRAFT REFUELING - A. A. Brailko (Научный вестник МГТУ ГА)
Much attention is payed to the tasks for ensuring domestic and international aircraft safety and regularity, which are multifaceted and complex. One of them is the system of ensuring the quality of aviation fuel for refueling aircraft at airports. A significant influence of the quality, chemical composition and fuel range on the reliability and lifetime of components and parts of the aircraft fuel system was studied in the process of development and experience accumulation of aircraft operating, processes of aviation fuel production, as well as during storage, quality control, transportation, refueling preparation and aircraft refueling. Currently, work is being done to study the influence of fuel quality on the units of the technological scheme of fuel-filling complexes, which provide the required cleanliness of the fuel according to the regulations. The article describes the trend level of aviation fuel cleanliness at the stages from receipt to issuance to the refueling station. The evaluation of compliance with existing regulations on the level of jet fuel cleanliness and the efficiency of fuel cleaning facilities is carried out. It is stated that one of the problems of insufficient level of aviation fuel cleaning quality is a violation of the acceptable contamination level of the fuel before the filter. It was found that the disadvantage of the used filter paper is the fiber wash out process. According to this research it was found that while cleaning fuel from mechanical admixtures it is necessary to take into account the technical condition of the filtering element, and proposal was developed for fuel-filling systems to ensure aviation fuel cleanliness in compliance with regulations.